2018
DOI: 10.1159/000492625
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combined Treatment with MLC601 (NeuroAiDTM) and Rehabilitation on Post-Stroke Recovery: The CHIMES and CHIMES-E Studies

Abstract: Background and Purpose: MLC601 has been shown in preclinical studies to enhance neurorestorative mechanisms after stroke. The aim of this post hoc analysis was to assess whether combining MLC601 and rehabilitation has an effect on improving functional outcomes after stroke. Methods: Data from the CHInese Medicine NeuroAiD Efficacy on Stroke (CHIMES) and CHIMES-Extension (CHIMES-E) studies were analyzed. CHIMES-E was a 24-month follow-up study of subjects included in CHIMES, a multi-centre, double-blind placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Subanalyses of the large clinical trial showed larger treatment effects among patients with predictors of poor outcome, including worse baseline NIHSS, likely because they had more potential to benefit from treatment [26,34,35]. A more recent analysis demonstrated that among patients who perform persistent rehabilitation, the use of this dietary supplement increased 10 Stroke Research and Treatment the rate of functional independence at 3 months and sustained over 2 years compared to rehabilitation alone [36]. This benefit was not seen among patients who did not consistently perform rehabilitation, suggesting that neurorestorative therapies work better when the brain is primed by rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Subanalyses of the large clinical trial showed larger treatment effects among patients with predictors of poor outcome, including worse baseline NIHSS, likely because they had more potential to benefit from treatment [26,34,35]. A more recent analysis demonstrated that among patients who perform persistent rehabilitation, the use of this dietary supplement increased 10 Stroke Research and Treatment the rate of functional independence at 3 months and sustained over 2 years compared to rehabilitation alone [36]. This benefit was not seen among patients who did not consistently perform rehabilitation, suggesting that neurorestorative therapies work better when the brain is primed by rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…It was first registered by the Sino Food and Drug Administration in 2001 after initial clinical trials done in China reported that MLC601 has improved functional outcome and recovery from post-stroke disability [7]. Over the next few years, many studies have reported on the benefits of MLC601, including a double-blind, placebo-controlled pilot study to investigate the potential efficacy of MLC601 in enhancing post-stroke recovery, which indicated that some positive trends were observed in the MLC601 group, and thus it may be useful for post-stroke rehabilitation [3, 4, 8, 9]. With regards to its safety profile, long-term laboratory data (biochemical, haematological, or electrocardiogram tests) confirms safety of MLC601 in acute stroke patients receiving a 3-month treatment, with no risk of increased haemorrhage [10, 11].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Accumulating evidence from animal studies 3640,54 and clinical trials 17,22,23,26,28,29,31,55 indicates that MLC601 and its derivative product MLC901 probably represent a promising therapeutic strategy for brain injuries, and particularly for stroke treatment. The molecular and cellular mechanisms associated with the beneficial effects of this TCM in cellular and animal models of stroke are multifaceted.…”
Section: Discussionmentioning
confidence: 99%